GAMBARAN TINGKAT PENGETAHUAN DAN PERILAKU MASYARAKAT TENTANG SWAMEDIKASI DI RT 01 RW 02 DESA TAMAN RAHAYU KECAMATAN SETU KABUPATEN BEKASI - Siska Shintia; Tisa Amalia; Ayu Izzatin Haifa (INKOFAR, 2025)
Health is a healthy condition of a person both physically, mentally, and socially, which is not only free from disease to enable him/her to live productively. One way for people to maintain health is through self-medication, which is the act of treating themselves. Self-medication is generally done to overcome complaints or minor illnesses such as fever, pain, dizziness, cough, influenza, stomach ulcers, worms, diarrhea, and other skin diseases. Self-medication must be done in a way that is appropriate for the disease experienced. Its implementation must meet the criteria for rational drug use, including the right choice of drugs, the right dose of drugs, no side effects, no contraindications, no drug interactions, and no polypharmacy. In practice, the use of drugs and drug doses, if errors occur continuously for a long time, is feared to pose a health risk. This study aims to determine the level of knowledge and behavior of the community about self-medication in RT 01 RW 02 Taman Rahayu Village, Setu District, Bekasi Regency. This type of research is descriptive quantitative with a cross-sectional approach method, using a questionnaire measuring instrument. Sampling was conducted using purposive sampling method that has met the inclusion and exclusion criteria of 85 respondents. The results of this study indicate the number of respondents who have good, sufficient, low levels of knowledge with percentages of 80%, 13%, and 7% respectively. The results of self-medication behavior measurements indicate that respondents who have appropriate, less, and inappropriate levels of behavior with percentages of 84%, 16%, and 0% respectively. Based on the results of the study, it can be concluded that the description of the level of knowledge and behavior of the community about self-medication in RT 01 RW 02 Taman Rahayu Village, Setu District, Bekasi Regency is good 80% and appropriate 84%.